Digital Shift : The Cultural Logic of Punctuation - Scheible, Jeff, 1982- (Book collections on Project MUSE., 2015)
Emoticons matter: Equal signs do, too. This book takes them seriously and shows how and why they matter. Digital Shift explores the increasingly ubiquitous presence of punctuation and typographical marks in our lives - using them as reading lenses to consider a broad range of textual objects and practices across the digital age. Jeff Scheible argues argues that pronounced shifts in textual practices have occurred with the growing overlap of crucial spheres of language and visual culture, that is as screen technologies have proliferated and come to form the interface of our everyday existence. Specifically, he demonstrates that punctuation and typographical marks have provided us with a rare opportunity to harness these shifts and make sense of our new environment. He does so through key films and media phenomena of the twenty-first century, from the popular and familiar to the avant-garde and the obscure. -- from back cover.